Classification of Multipurpose Tree Species on the Basis of their Growth Attributes under Tree/Crop Interface in Semi-arid Conditions: a Clustering Approach - Gill, A. S.; , Ajit (Indian Forester, 2004)
In a field study the polar and circular growth attributes of 12 MPTs has been analysed for six years from 1989-1990 to 1994-1995 averaging over the three spacings. Attempts has been made for classification of MPTs into fast, medium and slow growing categories through cluster analysis approach using growth variables. Growth of fast growing MPTs has been compared in silviculture and agrisilviculture conditions. The results revealed that Madhuca latifolia and Syzygium cumini clubbed into one group (cluster) when clustering was done on the basis of tree height and this class may be termed as slow growing; Eucalyptus tereticornis, Leucaena leucocephala, Acacia cupressiformis and Acacia nilotica clubbed into the second group (cluster) that may be called the fast growing; while the rest of the six species clubbed into the third medium growing group. However, when the clustering was done with respect to collar diameter, Casuarina equisetifolia and Hardwickia binata also joined the slow growing cluster of Syzygium cumini and Madhuca latifolia, whereas only Eucalyptus tereticornis, Leucaena leucocephala and Albizia lebbek clubbed into the fast growing group. Thus, if both criteria of polar and circular growth are considered simultaneously for clustering, only Eucalyptus tereticornis and Leucaena leucocephala falls into fast growing cluster and only Madhuca latifolia and Syzygium cumini belongs to the slow growing class while all the remaining eight MPTs categorized into medium growing. At the age of six years. the MAl of height was maximum in Eucalyptus (2.14 m/year) followed by Leucaena (1.39 m/year), while Madhuca latifolia (0.44 m/year) and Syzygium cumini (0.65 m/year) ranked at the bottom. The same pattern was visible for collar diameter with maximum for Eucalyptus (3.32 cm/year) followed by Leucaena (2.73 cm/year) and minimum for Casuarina (0.69 cm/year) and Madhuca (0.72 cm/year). Within the fast growing cluster Eucalyptus outperformed Leucaena, and the average growth performance of Eucalyptus was better in agrisilviculture over silviculture.